P092: Volunteer engagement in the emergency department: A scoping review. (May 2019) - Glanz, S.; Ellis, B.; Nelson, M.; Thompson, C.; McLeod, S.; Melady, D.
Abstract : Introduction : Little is known about the variety of roles volunteers play in the emergency department (ED), and the potential impact they have on patient experience. The objective of this scoping review was to identify published and unpublished reports that described volunteer programs in EDs, and determine how these programs impacted patient experiences or outcomes.Methods : Electronic searches of Medline, EMBASE, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews and CINAHL were conducted and reference lists were hand-searched. A grey literature search was also conducted (Web of Science, ProQuest, Canadian Business and Current Affairs Database ProQuest Dissertations and Theses Global). Two reviewers independently screened titles and abstracts, reviewed full text articles, and extracted data.Results : The search strategy yielded 4, 589 potentially relevant citations. After eliminating duplicate citations and articles that did not meet eligibility criteria, 87 reports were included in the review. Of the included reports, 18 were peer-reviewed articles, 6 were conference proceedings, 59 were magazine or newspaper articles, and 4 were graduate dissertations or theses. Volunteer activities were categorized as non-clinical tasks (e.g., provision of meals/snacks, comfort items and mobility assistance), navigation, emotional support/communication, and administrative duties. 52 (59.8%) programs had general volunteers in the ED and 35 (40.2%) had volunteers targeting a specific patient population, including pediatrics, geriatrics, patients with mental health and addiction issues and other vulnerable populations. 20 (23.0%) programs included an evaluative component describing how ED volunteers affected patient experiences and outcomes. Patient satisfaction, follow-up and referral rates, ED and hospital costs and length of stay, subsequent ED visits, medical complications, and malnutrition in the hospital were all reported to be positively affected by volunteers in the ED.Conclusion : This scoping review demonstrates the important role volunteers play in enhancing patient and caregiver experience in the ED. Future volunteer engagement programs implemented in the ED should be formally described and evaluated to share their success and experience with others interested in implementing similar programs in the ED.